SaRS-CoV-2: epidemiological characteristics, clinical characteristics, diagnosis and prevention – a review of current knowledge - Fisekovic Kremic, Marina; Stojanovic Ristic, Snezana (Srpski medicinski časopis Lekarske komore, 2021)
The outbreak of SARS-Cov-2 infection has been declared a global emergency. In addition to the most important issue public health and SARS-Cov-2 patients, an epidemic has significant effects on all aspects of life. The objective of this review articles is to summarize previous research on epidemiological characteristics, etiology, clinical characteristics, diagnosis, prevention and control of new SARS-Cov-2 infection. SARS-Cov-2 virus is a Beta coronavirus, a single- stranded RNA viruses. The envelope have a crucial role in the pathogenicity of the virus. A viral infection can cause an excessive immune response in the patient, which is labeled as a “cytokine storm,” whose effect is extensive tissue damage. Three main ways are of virus transmission, droplets, direct contact, aerosol. The incubation period is considered to be 1-14 days after exposure to the virus, an average of 5.2 days. The clinical manifestation ranges from asymptomatic, mild to severe, and some cases end in death. The main clinical manifestations include fever, cough, and shortness of breath. Nasal congestion, runny nose, sore throat, myalgia, diarrhea, loss of sense of taste and / or smell have been reported in a small number of cases. Diagnostic procedures are clinical manifestation, chest X- rays, biochemical analyzes, epidemiological anamnesis. For etiological diagnosis is used a positive nasopharyngeal or oropharyngeal swab (PCR for SARS-Cov-2, Ag test). SARS-Cov-2 infection has affected a large number of people and countries around the world. Early identification of infected persons, their isolation, use of preventive measures and the development of the vaccine are currently the most effective treatment in the contest against this virus. After finishing of the pandemic, it will be possible to estimate the health, social and economic impact of the virus.
Keywords: SARS-Cov-2; virus; pandemic; prevention